Universal behavior of coupled order parameters below three dimensions - Borchardt, Julia; Eichhorn, Astrid (Physical review, 2016)
We explore universal critical behavior in models with two competing order parameters, and an O(N) ⊕O(M) symmetry for dimensions d≤3. In d=3, there is always exactly one stable renormalization group fixed point, corresponding to bicritical or tetracritical behavior. Employing pseudospectral techniques to solve functional renormalization group equations in a two-dimensional field space, we uncover a more intricate structure of fixed points in d<3, where two additional bicritical fixed points play a role. Towards d=2, we discover ranges of N=M with several simultaneously stable fixed points, indicating the coexistence of several universality classes.
Gesehen am 21.11.2017